Quenching and tempering effects on Rheo-cast F357 aluminium alloy during Nd: YAG laser welding - Theron, Maritha (Centre for Materials Engineering, 2017)
Al-Si-Mg casting alloys are being used in automotive applications, aerospace applications and other applications requiring heat-treatable permanent mould castings that combine good weldability with high strength and toughness (ASM). These casting alloys are also known for their excellent castability, corrosion resistance and, in particular, .a range of mechanical properties in the heattreated condition. A357 aluminum alloy has been extensively used for semi-solid processing for more than three decades, and a large amount of components like fuel rails, engine mounts, engine brackets and suspension parts have been produced. This alloy is also included in the Statement for Work between the Council for Scientific and Industrial Research (CSIR) and Boeing Co, USA. F357, a hypo-eutectic aluminium alloy, Al-7%Si-0.6%Mg without beryllium, was processed with CSIR-Rheo technology to the Semi-Solid Metal (SSM) state and cast in plates with a 50 Ton High Pressure Die Casting machine. The castings were either left in the as-cast (F) condition or subjected to T4, T4+ or T6 heat treatments prior to laser welding. Welding of aluminium alloys poses many problems like porosity, loss of alloying elements, poor bead geometry and softening of the heat affected zone. Laser welding is however widely used in industrial production owing to the advantages such as low heat input, high welding speed and high production rate. Due to these unique advantages, the potential of autogenous Nd: Y AG laser welding as manufacturing process for this cast aluminium alloy was evaluated. A welding operating window was established and the optimum parameters were found to be a laser power of 3.8 kW at the workpiece and a welding speed of 4 m/min with a twin spot laser light configuration. These laser welding parameters were applied for the welding of the heat treated plates and resulted in very low weld joint porosity and almost no loss of alloying elements. The mechanical properties of age-hardenable Al-Si-Mg alloys are dependent on the rate at which the alloy is cooled after the solution heat treatment Because of the high cooling rate during laser welding, the possibility of producing weld seams through deep penetration laser welding, with mechanical properties matching those of the T6 temper condition, but without a post-weld solid solution heat treatment, was investigated. The quench rate after laser welding was measured and compared well with that measured after solution treatment. The resulting mechanical properties of F357 aluminium welded in the T4 condition and only artificially aged after welding (T4+ condition), compares very well with the T6 base material properties. The strengthening mechanisms obtained during laser welding and the different heat treatments were studied by means of transmission electron microscopy (TEM) and are consistent with the expected precipitation hardening processes in Al-Si-Mg alloys. The quench sensitivity of SSM F357 aluminium alloy is thus sufficiently low to obtain such an increase in strength values during laser welding, that no postweld solution heat treatment is necessary to achieve mechanical properties to the T6 performance specification.